2019
DOI: 10.1038/s41598-018-36521-x
|View full text |Cite
|
Sign up to set email alerts
|

Low Cost and Lithography-free Stamp fabrication for Microcontact Printing

Abstract: Microcontact printing (µCP) is a commonly used technique for patterning proteins of interest on substrates. The cells take the shape of these printed patterns. This technique is used to explore the effect of cellular morphology on their various functions such as survival, differentiation, migration, etc. An essential step for µCP is to fabricate a stamp from a silicon mould, prepared using lithography. Lithography is cost intensive and needs a high level of expertise to handle the instrumentation. Also, one st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 29 publications
(26 reference statements)
0
36
0
Order By: Relevance
“…Another field that broadly employs MSAs is the surface pattering of small molecules and proteins, which are found in a wide range of applications such as biosensors [ 73 ], disease diagnostic tools like detection of COVID-19 [ 74 , 75 ], cell culturing [ 40 , 76 , 77 , 78 ], and other analytical experiments [ 79 ]. Explicitly, PDMS MSAs are widely used because of their low cost of ownership and inherent hydrophobicity, which provides a favored surface for protein adsorption [ 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…Another field that broadly employs MSAs is the surface pattering of small molecules and proteins, which are found in a wide range of applications such as biosensors [ 73 ], disease diagnostic tools like detection of COVID-19 [ 74 , 75 ], cell culturing [ 40 , 76 , 77 , 78 ], and other analytical experiments [ 79 ]. Explicitly, PDMS MSAs are widely used because of their low cost of ownership and inherent hydrophobicity, which provides a favored surface for protein adsorption [ 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…PDMS is known to shrink when cured 36 , 37 , and this shrinking may contribute to the differences observed. Recently Khadpekar et al showed that the width of the imprinted spots also depends on the weight applied onto the stamp during 38 . Adding a weight onto the stamps during stamping is expected to improve the transfer of the chemical from the PDMS pillar to the surface.…”
Section: Discussionmentioning
confidence: 99%
“…Requirements for microfluidic devices are well established, scalability [9], reproducibility [10], and user-friendly characteristics to quickly move from lab-based prototyping to commercial manufacturing [11] are commonly specified. Typical microchips production may entail, for example, photolithography [12], microcontact printing [13][14][15], replica molding [16], or, as we show here, laser ablation.…”
Section: Introductionmentioning
confidence: 86%